2009
DOI: 10.4054/demres.2009.20.23
|View full text |Cite
|
Sign up to set email alerts
|

The correlates of infant and childhood mortality

Abstract: This paper has two main goals. The first is to review the context for studying infant mortality, which includes a review of the theoretical framework, the covariates used to examine mortality over the first 60 months of life, and the major findings of empirical studies. Second, the paper adds some new empirical evidence that comes from the longitudinal reconstitution of church registers of Bejsce parish, located in the south of Poland. This rich database allows for an analysis of mortality trends of cohorts bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 47 publications
(78 reference statements)
2
11
0
Order By: Relevance
“…Tymicki (2009) studied Polish data from the eighteenth to the twentieth centuries and found no association between child survival and parental age. Robine et al (2003) found no association between parental age and the probability of surviving to age 100.…”
Section: Discussionmentioning
confidence: 99%
“…Tymicki (2009) studied Polish data from the eighteenth to the twentieth centuries and found no association between child survival and parental age. Robine et al (2003) found no association between parental age and the probability of surviving to age 100.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond studies that focus on Ghana, other correlates of infant mortality identified in the literature for national and subnational levels include presence of parents and other family members, season of a child’s birth, sex of the child, age of mother at birth, multiple versus single births, birth location, birth rank, the number of siblings, mortality of older siblings, and mothers’ occupation in India and China [47] , [48] , [49] , inequality in 145 countries [50] , primary care physician supply in the US states [51] , wages and housing density in New Zealand [52] , public spending on health, GNI/capita, poverty rate, income equality, and young female illiteracy rate in 152 countries [53] . Additional correlates include neighborhood sanitation in India [54] , income distribution is six countries in West Africa [55] , access to improved sources of drinking water, improved toilet facilities, antenatal care, and skilled delivery in Nigeria [56] , access to primary care and conditional cash transfers in Brazil [57] .…”
Section: Introductionmentioning
confidence: 99%
“…The subnational studies [47] , [48] , [51] , [52] , [51] , [56] , [57] revealed significant cross-regional disparities in the determinants of infant mortality that the national studies [49] , [50] , [53] , [55] could not have accounted for. For instance, the subnational study in rural India [48] found that the infant mortality rate for males was 113 and that for females was 90.…”
Section: Introductionmentioning
confidence: 99%
“…The covariates used for this study are residence, nature of the child, sex of the child, mother follow-up, place of antenatal care, place of child delivery, breastfeeding from the breast only, a child infected with malaria, the child suffered from malnutrition, the child suffered from septicemia, a child suffered from cough and child suffered from pneumonia. The variables classi cations used in the current study were suggested by many previous studies [15,16,17,18,19,20,21,22,23,24]…”
Section: Independent Variablesmentioning
confidence: 99%